Determination antioxidant (ascorbic acid) in different type of fruits / Rosmawati Md Zin - Md Zin, Rosmawati (Faculty of Applied Sciences, 2009)
Eat fruit as a good natural source of anti-oxidants which help to prevent the dangers of free .Antioxidants protected cells from the damage caused by highly reactive molecules known as free radicals which have been linked to health problems including cancer, Alzheimer's, and cardiovascular diseases. Antioxidants reacted with and effectively neutralize these free radicals as far as their damaging health impacts are concerned. Although free radicals were part of the natural cell metabolic processes, the body does not 100% effectively remove them particularly as one gets older. Eating antioxidants like the fruit antioxidants helps the body make up the difference.